Novel Coating of Surgical Suture Confers Antimicrobial Activity Against Porphyromonas gingivalis and Enterococcus faecalis. Issue 6 (1st June 2015) - Meghil, Mohamed M.; Rueggeberg, Frederick; El‐Awady, Ahmed; Miles, Brodie; Tay, Franklin; Pashley, David; Cutler, Christopher W.
Abstract : Background: The oral cavity is colonized by >10 9 bacteria, many of which can increase heart disease risk when seeded into the bloodstream. Most dentoalveolar surgeries require the use of surgical sutures. Suture placement and removal can increase the risk of postoperative infection and bacteremia. The aim of this study is to evaluate the antimicrobial activity of a novel quaternary ammonium compound, K21, when coated on different suture materials. Methods: The periodontal pathogen Porphyromonas gingivalis and the endodontic species Enterococcus faecalis were grown to early log phase and inoculated on enriched Brucella blood agar, on which were placed identical lengths of surgical suture (chromic gut, polyester suture, silk, and nylon suture) and control unwaxed dental floss impregnated with K21 at 5%, 10%, 20%, and 25% volume/volume in ethanol vehicle. Controls included the following: 1) sutures treated with vehicle; 2) untreated sutures; and 3) unwaxed floss. Zones of inhibition in millimeters were measured at five randomized sites per suture/floss for each concentration and material used. Mean ± SD of zones of inhibition were calculated, and analysis of variance ( P <0.05) was used to determine whether differences were statistically significant. Results: The results indicate that K21‐coated suture at concentrations ranging from 5% to 25%, depending on the type of suture, have antimicrobial activity for P. gingivalis and E. faecalis . Nylon suture coated with K21 at 5%, 10%, 20%, and 25% resulted in zones ranging from 3 to 11 mm. Polyester suture was more effective at lower K21 concentrations with 5% ( P = 0.0031), 10% ( P = 0.0011), and 20% ( P = 0.0002), yielding 7.5, 8.3, and 10.5 mm zones of inhibition. K21‐coated silk suture yielded significant zones of inhibition at 25% ( P <0.0001), whereas chromic gut was effective at K21 concentrations of 5% ( P = 0.0081) and 25% ( P <0.0001). Conclusion: It is concluded that K21‐coated surgical sutures have antimicrobial activity for bacterial species of direct relevance to postoperative infection and bacteremia.